Analisis pemeliharaan dan pelestarian bahan pustaka di Perpustakaan Sekolah Menengah Kejuruan Swakarya Palembang - Rhoni Rodin; Kana Kurnia (Al-Kuttab : Jurnal Kajian Perpustakaan, Informasi dan Kearsipan, 2021)
This paper aims to analysis the maintenance and preservation of library materials at SMK Swakarya Palembang’s Library, dealing with: first, the factors that cause damage to library materials at SMK Swakarya Palembang’s Library. Second, how to prevent damage to library materials at SMK Swakarya Palembang’s library. Control in the maintenance and preservation of library materials in SMK Swakarya Palembang’s library. Data obtained through observation and interviews with library managers. From the analysis and discussion, the results were found as follows: first, damage to library materials was caused by physical, biological, and chemical factors. Second, the maintenance of library materials is not optimal, such as cleaning books from dust using a duster and a dry cloth. Third, SMK Swakarya Palembang’s library does not have librarians or expert staff in the field of libraries, and there is a lack of funds and there is no policy from the library manager. Based on the above conclusions, it is suggested that SMK Swakarya Palembang’s library has librarian experts in managing libraries and schools should pay attention to funds for preserving library materials.